New multicast technology (BIER) and prototype system - Jinghai YU; Zheng ZHANG; Shaofu PENG (Dianxin kexue)
The principle and advantages of BIER were introduced,and it was compared with traditional multicast technology.It was pointed out that BIER technology was an important choice for future network evolution.At the same time,through the introduction of the prototype system,the feasibility of the BIER and the evolution capability were analyzed in detail.It was predicted that BIER technology was an inevitable choice of controllable multicast under the trend of SDN evolution.